LAN cable
The LAN cable design with a non-halogen resin composition and optimized insulating layer achieves smaller diameter and high flame retardancy without flame retardant tape, addressing the challenge of size and safety in railway applications.
Patent Information
- Application Number
- JP2024077672
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-12-08
AI Technical Summary
Existing LAN cables face challenges in achieving smaller diameters while maintaining high flame retardancy, particularly in railway vehicle applications, due to the need for flame retardant tapes that increase thickness.
A LAN cable design featuring a twisted wire pair covered by a sheath made of a non-halogen flame-retardant resin composition containing a specific ratio of metal hydroxide and carbon black, without the use of flame retardant tape, and an insulating layer with a dielectric constant of 2.5 or less, allowing for a diameter of 8.8 mm or less.
The design achieves high flame retardancy and smaller diameter, ensuring compliance with EN standards and improved transmission characteristics, while maintaining physical properties such as strength and low-temperature performance.
Smart Images

Figure 0007619512000004 
Figure 0007619512000005 
Figure 0007619512000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a LAN cable. [Background technology]
[0002] A LAN cable is a cable used to construct a LAN (Local Area Network). This LAN cable is configured with a sheath that covers the outer periphery of an insulated wire having an insulating layer formed on the outer periphery of a conductor, and a sheath made of a halogen-free flame-retardant resin composition is known.
[0003] In particular, LAN cables for railway vehicles may be required to have extremely high flame retardancy that satisfies the fire safety (single-strand flame retardancy test) of the EN standard, a unified European standard, and the cables also need to satisfy other physical properties such as strength, elongation, and low-temperature characteristics.
[0004] When such high flame retardancy is required, it is generally considered to add a large amount of flame retardant, but if the amount of flame retardant is too high, the physical properties of the sheath will deteriorate, making it difficult to provide a LAN cable that satisfies these characteristics with the sheath alone.
[0005] Therefore, a LAN cable that satisfies the above-mentioned characteristics is known in which a flame-retardant tape such as a polyimide film is placed between the insulated wire and the sheath that covers its outer circumference, and the sheath is cross-linked to a predetermined degree, so that the LAN cable as a whole satisfies the above-mentioned characteristics (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2021-64623 Summary of the Invention [Problem to be solved by the invention]
[0007] Incidentally, in recent years, there has been a demand for such LAN cables to be made thinner. However, since high flame retardancy must be ensured for the above-mentioned applications, the flame-retardant tape provided between the sheath and the insulated wire cannot be omitted, and there has been a limit to how thin the cables can be made.
[0008] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a LAN cable that can be made thinner and has high flame retardancy. [Means for solving the problem]
[0009] In one embodiment, a LAN cable includes a twisted pair wire formed by twisting together insulated electric wires having a plurality of insulating layers, and a sheath covering the outer circumference of the twisted pair wire, the LAN cable has an outer diameter of 8.8 mm or less, the sheath is made of a halogen-free flame-retardant resin composition containing a base polymer, a metal hydroxide, and carbon black, the metal hydroxide is contained in an amount of 180 to 190 parts by mass relative to 100 parts by mass of the base polymer, the carbon black is contained in an amount of 15 to 20 parts by mass relative to 100 parts by mass of the base polymer, the outer diameter of the insulated electric wire is 1.43 mm or less, the overall dielectric constant of the insulating layer is 2.5 or less, and the insulating layer is made of a halogen-free polymer. Also, the LAN cable may be free of a flame-retardant tape between the twisted pair wire and the sheath. Effect of the Invention
[0010] According to the LAN cable of one embodiment, it is possible to provide a LAN cable that can be made thin and that can ensure high flame retardancy. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic cross-sectional view of a LAN cable according to an embodiment of the present invention; [Diagram 2] FIG. 2 is a schematic cross-sectional view of a LAN cable according to a production example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, a LAN cable according to the present invention will be described with reference to an embodiment.
[0013] In addition, in all the drawings for explaining the embodiments, the same members are generally given the same reference numerals, and the repeated explanations are omitted. In order to make the drawings easier to understand, hatching may be omitted even in cross-sectional views. Similarly, hatching may be added even in plan views.
[0014] [LAN cable] A LAN cable according to the present embodiment will be described with reference to the drawings. Fig. 1 is a schematic cross-sectional view of the LAN cable according to the embodiment. As shown in Fig. 1, the LAN cable according to the present embodiment is a LAN cable 10 including a twisted pair wire formed by twisting together a plurality of insulated wires 3 each having an insulating layer 2 around the outer periphery of a conductor 1, a braid 4 provided so as to cover the outer periphery of the twisted pair wire, and a sheath 5 that further covers the braid 4. This LAN cable 10 is configured as a twisted pair wire formed by twisting together a plurality of insulated wires 3, and a shield 6 is provided around the outer periphery of the twisted pair wire.
[0015] In such LAN cables, the high flame retardancy required for flame retardancy tests such as those in the overseas standard EN45545 has traditionally been achieved by providing a specified flame retardant layer such as a flame retardant tape between the sheath 5 and the insulated wire 3 (directly below the sheath 5). However, the inclusion of this flame retardant tape results in a larger diameter cable.
[0016] In contrast, the LAN cable 10 of this embodiment can achieve flame retardancy that satisfies the above standards without using such flame-retardant tape, and the cable can be made thinner, making it a LAN cable that is particularly suitable for use in railway vehicles.
[0017] [Insulated wire] The insulated wire 3 is configured by providing an insulating layer 2 on the outer periphery of a conductor 1. The material of the conductor 1 is not particularly limited, and any known conductor can be used, for example, copper or a copper alloy, or aluminum or an aluminum alloy. The configuration of the conductor 1 is also not particularly limited, but in addition to a single wire, it is preferable to adopt a twisted wire structure in which multiple wires are twisted together, taking into account the flexibility of the cable. In addition, it is also possible to appropriately apply plating to the conductor, and for example, it is also possible to cover it with tin plating or the like.
[0018] The material of the insulating layer 2 is not particularly limited, but is preferably polyethylene, and more preferably polyethylene with a dielectric constant of 2.5 or less. When the dielectric constant of polyethylene is 2.5 or less, the capacitance of the insulating layer is small. This further improves the transmission characteristics of the LAN cable. The dielectric constant of the entire insulating layer is preferably 2.5 or less. In this case, the transmission characteristics of the LAN cable are further improved. The dielectric constant of the entire insulating layer is more preferably 1.9 to 2.3, and even more preferably 1.9 to 2.1.
[0019] Examples of polyethylene include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), linear very low-density polyethylene (VLDPE), high-density polyethylene (HDPE), etc., and more preferably low-density polyethylene, and particularly preferably low-density polyethylene having a density of 0.930 or less and an MFR (melt flow rate) of 0.30 or less. Any one of the above polyethylenes may be used alone, or two or more may be blended together.
[0020] The insulating layer 2 may further contain an antioxidant, a copper inhibitor, a colorant, etc. The amounts of the antioxidant, copper inhibitor, colorant, etc. added are not particularly limited, but are preferably such that the dielectric constant of the entire insulating layer 2 is 2.5 or less. The amount of the colorant, etc. added is preferably 5 mass % or less, more preferably 2 mass % or less. Furthermore, the insulating layer 2 may not contain a flame retardant. By using a sheath having the characteristics described below, a LAN cable 10 that satisfies high flame retardancy can be realized even if the insulating layer 2 is a resin composition that does not contain a flame retardant.
[0021] Here, the polyethylene may be foamed using a known method. For example, the polyethylene can be foamed using an inert gas such as nitrogen or a chemical foaming agent such as ADCA (azodicarbonamide). The foaming degree of the polyethylene is preferably 15% by mass or more.
[0022] [Twisted pair wire] The twisted pair is formed by twisting together a number of insulated wires 3. As described above, the LAN cable 10 is characterized by having a twisted pair. The LAN cable 10 shown in FIG. 1 shows an example in which the LAN cable 10 has four twisted pairs, each of which is made up of two insulated wires 3.
[0023] At this time, the outer diameter r of the insulated wire constituting the twisted pair is, for example, 1.43 mm or less, and the shield 6 is provided on the outside of the core. In this embodiment, the sheath 5 is made of a resin composition with sufficient flame retardancy. Therefore, in order to achieve another object of reducing the diameter of the LAN cable 10, it has been found that it is possible to ensure the flame retardancy of the LAN cable even if the outer diameter r of the insulated wire is reduced as described above and the outer diameter of the LAN cable is reduced. This makes it possible to obtain a LAN cable 10 that has a small diameter and is highly flame retardant, which has never been achieved before. In addition, by reducing the outer diameter r of the insulated wire, the amount of the insulating layer, which is flammable and is used in the insulated wire 3, can be reduced, which also has a positive effect in terms of ensuring the flame retardancy of the LAN cable 10.
[0024] The shield 6 is constructed by wrapping around the twisted pair wires, and can be, for example, a shielding tape having a base layer made of a resin such as polyethylene terephthalate molded into a tape shape, and a metal layer made of a metal foil such as aluminum foil attached to the surface of the base layer.
[0025] In addition, although the insulating layer 2 may be a foamed layer in the above description, it may also be a multi-layered insulating layer including a foamed layer. When the insulating layer 2 of this multi-layered structure has a three-layered structure of an inner layer, an intermediate layer, and an outer layer from the conductor 1 side, it is preferable that the inner layer and the outer layer are configured as coating layers (skin layers) and the intermediate layer is a foamed layer. By combining the skin layer and the foamed layer in this way, the outer diameter of the insulated electric wire 3 can be reduced, and the LAN cable can be made thinner. Furthermore, by making the insulating layer 2 have such a three-layered structure, the dielectric constant can be improved because of the foamed portion (air).
[0026] As described above, this insulating layer 2 can be formed, for example, from a polyethylene material. For example, the inner layer and outer layer can be made of polyethylene coating layers (skin layers) and the intermediate layer can be a polyethylene foam layer, so that the inner layer, intermediate layer and outer layer can all be made of polyethylene.
[0027] In this case, the thickness of the intermediate layer is preferably 0.25 mm to 0.4 mm, more preferably 0.25 mm to 0.35 mm, and the total thickness of the three-layer structure is preferably 0.35 mm to 0.45 mm.
[0028] [Braid] Braid 4 is made by braiding a plurality of metal wires together, and is provided to reduce noise in LAN cable 10 and to improve the strength of LAN cable 10 itself. Braid 4 is, for example, a cross braid. Metal wires that make up braid 4 may be made of copper, copper alloy, or the like.
[0029] 〔sheath〕 The sheath 5 is made of a halogen-free resin composition containing a base polymer, a metal hydroxide, and carbon black. In this embodiment, these components are mixed in a specific ratio, and each component will be described in detail below.
[0030] (Base polymer) The base polymer includes polyolefins, maleic anhydride modified polyolefins and ethylene vinyl acetate copolymers.
[0031] (1) Polyolefin The polyolefin used here has a melting point of 110° C. or higher. The melting point can be determined by differential scanning calorimetry (DSC). By using this polyolefin having a melting point of 110° C. or higher, the oil resistance of the sheath 5 can be improved.
[0032] In the oil resistance test, a test piece is immersed in IRM902 test oil heated to 100℃ for 72 hours, and then the tensile properties are examined to see how much the tensile properties after immersion have changed from the tensile properties before immersion. For example, if the melting point is below 110℃, the crystals melt during the oil resistance test, making it difficult to prevent the oil from diffusing, and the rate of change in the tensile properties increases.
[0033] Examples of polyolefins having a melting point of 110°C or higher include low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, polypropylene, etc. However, high-density polyethylene has too high a degree of crystallinity and thus has low elongation at break, and polypropylene is prone to collapse in crosslinking such as by electron beam irradiation. In order to obtain a balance of properties, it is preferable to use low-density polyethylene, and it is more preferable to use linear low-density polyethylene.
[0034] (2) Maleic anhydride modified polyolefin Maleic anhydride modified polyolefin is a polyolefin modified with maleic anhydride.
[0035] Examples of polyolefins that can be used as the material to be modified include ethylene-α-olefins such as low-density polyethylene, linear low-density polyethylene, very low-density polyethylene, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butene-1 copolymer, ethylene-hexene-1 copolymer, and ethylene-octene-1 copolymer.
[0036] The method for modifying a polyolefin with maleic anhydride is not limited, and the polyolefin can be obtained by a reaction using heat alone. Furthermore, the maleic anhydride in the maleic anhydride-modified polyolefin may be graft copolymerized or block copolymerized.
[0037] The amount of maleic anhydride modified polyolefin added is 10 to 35 parts by mass per 100 parts by mass of the base polymer. If it is less than 10 parts by mass, the required low-temperature properties cannot be satisfied, and if it is more than 35 parts by mass, the initial elongation at break becomes insufficient.
[0038] In order to obtain even higher low-temperature properties, it is more preferable to add the maleic anhydride modified polyolefin in an amount of 25 to 35 parts by mass per 100 parts by mass of the base polymer.
[0039] (3) Ethylene-vinyl acetate copolymer By using ethylene vinyl acetate copolymer as the base polymer, an endothermic reaction occurs due to deacetylation during combustion, improving flame retardancy. High flame retardancy can be obtained by making the amount of acetic acid (amount of CH3COO-) in 100% by mass of the base polymer 2.3% by mass or more.
[0040] (metal hydroxide) The metal hydroxide used here is a flame retardant. For example, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, etc. can be used as the metal hydroxide. Among them, it is preferable to use aluminum hydroxide and magnesium hydroxide. The heat absorption amount during decomposition of calcium hydroxide is about 1000 J / g, whereas the heat absorption amount of aluminum hydroxide and magnesium hydroxide is 1500 to 1600 J / g, which is high. Therefore, the flame retardancy is improved by adding aluminum hydroxide or magnesium hydroxide.
[0041] Furthermore, it is preferable to use magnesium hydroxide, which has a higher decomposition temperature than aluminum hydroxide and therefore improves moldability.
[0042] The metal hydroxide may be surface-treated with a silane coupling agent, a titanate coupling agent, a fatty acid such as stearic acid, or the like in order to improve dispersibility.
[0043] The metal hydroxide is added in an amount of 180 to 190 parts by mass per 100 parts by mass of the base polymer. If the amount is less than 180 parts by mass, sufficient flame retardancy cannot be obtained, and if the amount is more than 190 parts by mass, the elongation at break decreases.
[0044] (Carbon Black) The carbon black used here is a flame retardant auxiliary. There is no particular limitation on the type of carbon black to be added, but in consideration of the breaking elongation, it is preferable to use FT or MT class carbon.
[0045] In order to ensure a certain level of flame retardancy, it is necessary to add a large amount of metal hydroxide as a flame retardant. However, adding a large amount of flame retardant may impair the mechanical properties of the resin composition. Therefore, carbon black is added as a flame retardant assistant. The amount of carbon black added is 15 to 20 parts by mass per 100 parts by mass of the base polymer. The more carbon black added, the more flame retardancy can be improved, but if the amount is more than 20 parts by mass, coarse particles are generated due to the aggregation of carbon black, and the initial breaking elongation and low-temperature properties are reduced.
[0046] (Other additives) In addition to the above materials, crosslinking agents, crosslinking assistants, ultraviolet absorbers, light stabilizers, softeners, lubricants, colorants, reinforcing agents, surfactants, inorganic fillers, antioxidants, plasticizers, metal chelating agents, foaming agents, compatibilizers, processing assistants, stabilizers, etc. may be added.
[0047] In addition, as the flame retardant assistant, a flame retardant assistant other than the carbon black may be added. As the flame retardant assistant, there are phosphorus-based flame retardant assistants such as red phosphorus and triazine-based flame retardant assistants such as melamine cyanurate, but they may generate phosphine gas or cyan gas, so they must be handled with care. Any flame retardant assistant other than these can be applied, and for example, clay, silica, zinc stannate, zinc borate, calcium borate, hydroxide dolomide, silicone, etc. can be used.
[0048] (Gel fraction) Gel fraction is a method for confirming the degree of cross-linking of a polymer. Here we explain how to measure gel fraction. First, weigh the sample (W1) and immerse it in xylene heated to 110°C for 24 hours. After immersion, leave it at atmospheric pressure at 20°C for 3 hours, and then vacuum dry at 80°C for 4 hours. The weight ratio of the sample after this (W2) to its weight before immersion in xylene (W1) ((W2 / W1) x 100, unit [%]) is defined as the gel fraction. If the gel fraction is less than 85%, it cannot be said that the oil resistance is sufficient.
[0049] The crosslinking treatment may be chemical crosslinking using an organic peroxide, a sulfur compound, or silane, irradiation crosslinking using an electron beam, radiation, or the like, or chemical crosslinking using other chemical reactions, and any of these crosslinking methods may be applied. Among these, irradiation crosslinking using an electron beam is more versatile than other irradiation crosslinking methods, and does not involve the risk of scorching during extrusion molding as occurs with chemical crosslinking, and is therefore preferably used as the crosslinking treatment of the present embodiment.
[0050] [Outer diameter of cable] In the present embodiment, the LAN cable 10 is characterized in that its outer diameter is 8.8 mm or less. As a result of careful consideration of the configuration of this highly flame-retardant cable, it was found that the thinner the outer diameter of the cable, the more likely it is to burn in a flame retardancy test such as EN45545.
[0051] The inventors have discovered for the first time that even under such conditions, it is possible to obtain a highly flame-retardant LAN cable that meets the flame retardancy requirements in the above-mentioned flame retardancy test, without using a flame-retardant tape and by reducing the diameter of the cable.
[0052] In this case, the thickness of the sheath 5 is preferably 0.68 mm to 0.92 mm, and more preferably 0.72 mm to 0.88 mm. If the thickness exceeds 0.92 mm, it is easy to ensure flame retardancy, but it becomes difficult to achieve the thin diameter required in this embodiment, and if it is less than 0.68 mm, there is a risk that sufficient flame retardancy cannot be ensured.
[0053] [LAN cable manufacturing method] The cable 10 of the present embodiment is manufactured, for example, as follows. First, a resin composition that will become the insulating layer 2 of the insulated wire is prepared, and then the conductor 1 is prepared. Then, the resin composition for the insulating layer is extruded by an extrusion molding machine so as to cover the periphery of the conductor 1, thereby forming the insulating layer 2 of a predetermined thickness. In this manner, the insulated wire 3 can be manufactured.
[0054] The insulating layer 2 can be formed using a general-purpose material, and is preferably a halogen-free polymer, such as polyolefins including high-density polyethylene, medium-density polyethylene, low-density polyethylene, linear low-density polyethylene, very low-density polyethylene, and ethylene-acrylic acid ester copolymers.
[0055] Rubber materials can also be used, such as ethylene-propylene copolymer rubber, ethylene-propylene-diene terpolymer rubber, acrylic rubber, ethylene-acrylate copolymer rubber, ethylene-octene copolymer rubber, ethylene-acrylate copolymer rubber, ethylene-octene copolymer rubber, ethylene-vinyl acetate copolymer rubber, ethylene-butene-1 copolymer rubber, butadiene-styrene copolymer rubber, isobutylene-isoprene copolymer rubber, and block copolymer rubber having a polystyrene block.
[0056] Furthermore, engineering plastics can also be used, such as polyethylene terephthalate, polybutylene terephthalate, polyphenylene ether, polycarbonate, polyamide, polyphenyl sulfide, polyether ether ketone, polyethylene naphthalate, polybutylene naphthalate, polyether sulfone, etc., and thermoplastic elastomers thereof can also be used. The base polymer of this insulating layer 2 can be a single polymer or a blend of two or more polymers.
[0057] In the insulating layer 2, the resin composition composed of these materials may contain, as necessary, a crosslinking agent, a crosslinking assistant, a flame retardant assistant, an ultraviolet absorber, a light stabilizer, a softener, a lubricant, a colorant, a reinforcing material, a surfactant, an inorganic filler, a plasticizer, a metal chelating agent, a foaming agent, a compatibilizer, a processing assistant, a stabilizer, etc.
[0058] In the present embodiment, after the insulated wire 3 is produced, the resin composition constituting the insulating layer 2 can be crosslinked by, for example, an electron beam crosslinking method or a chemical crosslinking method.
[0059] When the electronic crosslinking method is used, the resin composition is molded into the insulating layer 2 of the insulated wire, and then crosslinked by irradiation with an electron beam of, for example, 1 to 30 MRad. When the chemical crosslinking method is used, a crosslinking agent is added to the resin composition in advance, and the resin composition is molded into the insulating layer 2 of the insulated wire 3, and then crosslinked by heat treatment.
[0060] Two of the obtained insulated wires 3 are twisted together to form a twisted pair, and four of the twisted pairs having a shield 6 obtained by winding a shielding tape around the twisted pair are twisted together, and then the braid 4 is formed by a known method so as to cover the braid 4. Furthermore, the resin composition of the present embodiment is extruded around the outer periphery of the braid 4 thus obtained to form a sheath (covering layer) 5 of a predetermined thickness. In this manner, the cable 10 of the present embodiment can be manufactured. EXAMPLES
[0061] Next, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.
[0062] [Sheath material preparation examples 1-3] The sheath material was prepared according to the compositions shown in Tables 1 and 2. These compositions were kneaded in a pressure kneader until the temperature reached 220° C. to prepare pellets as the sheath material.
[0063] [Table 1]
[0064] [Table 2]
[0065] [Sheath material] In Table 1, the materials used are as follows: (Polymer) PE: Prime Polymer, SP1510 (Tm117℃) EVA: Evaflex EV45X, manufactured by Mitsui Dow Polychemicals Co., Ltd. Modified polyolefin: Toughma MH5040, manufactured by Mitsui Chemicals, Inc. (Flame retardant) Magnesium hydroxide: Konoshima Chemical Co., Ltd., Magsheath S4 Carbon black: Asahi Thermal, manufactured by Asahi Carbon Co., Ltd.
[0066] [Evaluation of Sheath Materials] The resulting resin composition was evaluated for the following properties.
[0067] (1-1) Flame retardancy of sheath material (VFT) The obtained resin composition was used to prepare a test cable for evaluating flame retardancy. This test cable was prepared as test cable 50 shown in Fig. 2, which was covered with a sheath material to a thickness of 0.8 mm and cross-linked by irradiation with a dose of 5 MRad to prepare a cable with an outer diameter of 5.8 mm.
[0068] The flame retardancy of the obtained test cables was evaluated by a vertical flame test in accordance with the standard EN60332-1-2. Those that passed were marked with "◯" and those that failed were marked with "X".
[0069] (1-2) Initial tensile test of sheath material A dumbbell specimen was prepared by peeling off the sheath from the test cable having the configuration shown in Fig. 2 obtained in the same manner as above. Next, a tensile test was performed using the test specimen at a tensile speed of 250 mm / min in accordance with EN60811-501. Regarding elongation, if the elongation was less than 125%, it was rated as × (fail), and if the elongation was 125% or more, it was rated as ○ (pass).
[0070] Regarding the tensile strength, if the tensile strength was less than 10 MPa, it was rated as × (fail), and if it was 10 MPa or more, it was rated as ○ (pass with a margin).
[0071] (1-3) Oil resistance test of sheath material A dumbbell specimen was prepared by peeling off the sheath from the test cable of the configuration shown in Fig. 2 obtained in the same manner as above. The specimen was immersed in IRM902 oil heated to 100°C for 72 hours in accordance with EN60811-404, and the specimen was pulled at a displacement rate of 250 mm / min to measure the load and elongation until breakage. The tensile strength change rate (A2 / A1) x 100 [%]) and the elongation change rate ((B2 / B1) x 100 [%]) were calculated from the tensile strength (A1) and elongation at break (B1) of the specimen before immersion in the test oil and the tensile strength (A2) and elongation at break (B2) of the specimen after immersion in the test oil. Those with a tensile strength change rate of 75 to 125% and a breaking elongation change rate of 65 to 135% were rated as good (◯), and those with a tensile strength change rate of 70 to 75% or 125 to 130% and a breaking elongation change rate of 60 to 65% or 135 to 140% were rated as fair (△).
[0072] (1-4) Fuel resistance test of sheath material A dumbbell specimen was prepared by peeling off the sheath from the test cable having the configuration shown in Fig. 2 obtained in the same manner as above. The specimen was immersed in IRM903 oil heated to 70°C for 168 hours in accordance with EN60811-404, and then pulled at a displacement rate of 250 mm / min to measure the load and elongation until breakage. The tensile strength change rate (A2 / A1) x 100 [%]) and the elongation change rate at break ((B2 / B1) x 100 [%]) were calculated from the tensile strength (A1) and elongation at break (B1) of the specimen before immersion in the test oil and the tensile strength (A2) and elongation at break (B2) of the specimen after immersion in the test oil. The specimens with a tensile strength change rate of 70 to 130% and a rupture elongation change rate of 60 to 140% were considered to pass (good).
[0073] (1-5) Low-temperature property test of sheath material The above test cables were subjected to low-temperature bending tests in accordance with EN60811-504. Tests were performed at -40℃ and -50℃ with N=2 for each condition. Cables that passed both tests (no cracks or breaks) were marked with an "O" and cables that passed only one test were marked with a "△".
[0074] [Example 1] Next, a LAN cable having the configuration shown in Figure 1 was fabricated as follows. A conductor with a diameter of 0.565 mm was coated with a 0.01 mm thick polyethylene layer as an inner layer, a 0.36 mm thick foamed polyethylene layer with a foaming degree of 30% as an intermediate layer, and a 0.05 mm thick polyethylene layer as an outer layer.
[0075] The above was subjected to irradiation and cross-linking at 22 Mrad to obtain an insulated wire having an outer diameter of 1.40 mm and an insulating layer of 0.42 mm in thickness.
[0076] Next, two of these insulated wires were twisted together (one pair) and an aluminum-laminated PET tape was attached vertically to create four pairs. The four pairs were twisted together and then covered with a copper braid. The sheath material of Preparation Example 1 shown in Table 1 was then coated to a thickness of 0.78 mm and cross-linked with an irradiation dose of 5 Mrad to obtain a LAN cable of Example 1 having the configuration shown in Figure 1.
[0077] [Example 2] Next, a conductor with a diameter of 0.565 mm was coated with a 0.01 mm thick polyethylene layer as an inner layer, a 0.30 mm thick foamed polyethylene layer with a foaming degree of 50% as an intermediate layer, and a 0.05 mm thick polyethylene layer as an outer layer.
[0078] The above was subjected to irradiation and cross-linking at 22 Mrad to obtain an insulated wire having an outer diameter of 1.30 mm and an insulating layer of 0.36 mm in thickness.
[0079] Next, two of these insulated wires were twisted together (one pair) and an aluminum-laminated PET tape was attached vertically to create four pairs. The four pairs were twisted together and then covered with a copper braid. The sheath material of Preparation Example 1 shown in Table 1 was then coated to a thickness of 0.78 mm and cross-linked with an irradiation dose of 5 Mrad to obtain a LAN cable of Example 2 having the configuration shown in Figure 1.
[0080] The configuration features of the obtained LAN cables are shown in Table 3, including the comparative examples described below.
[0081] [Comparative Example 1] As a conventional example, a LAN cable of Comparative Example 1 having the configuration shown in FIG. 1 was obtained using the sheath material of Example 1 as Preparation Example 3.
[0082] [Comparative examples A~C] In each of Examples 1 and 2 and Comparative Example 1, a LAN cable was produced in which a flame-retardant polyimide tape was wound horizontally between the copper braid and the sheath in a 1 / 4 wrap, and these LAN cables were designated Comparative Examples A to C, respectively.
[0083] [Table 3]
[0084] [Evaluation of LAN cables] The LAN cables obtained in Examples 1 and 2, Comparative Example 1, and Comparative Examples A to C were evaluated for flame retardancy (VFT), initial tensile test, oil resistance test, fuel resistance test, and low-temperature characteristic test using the same procedures and evaluation criteria as those used to evaluate the sheath material. In addition, the obtained LAN cables were also subjected to tensile tests after aging. The results are shown in Table 3.
[0085] (2-1) Tensile test of cable after aging The sheath was peeled off from the obtained cable to prepare a dumbbell specimen. Next, the test specimen was used and treated at 120℃ for 240 hours, and then pulled at a displacement rate of 250 mm / min to measure the load and elongation until breakage. The tensile strength change rate (A2 / A1) x 100[%]) and the elongation change rate at break ((B2 / B1) x 100[%]) were calculated from the tensile strength (A1) and elongation at break (B1) of the test specimen before heat treatment and the tensile strength (A2) and elongation at break (B2) of the test specimen after heat treatment. For the evaluation, a tensile strength change rate of 70-130% and a rupture elongation change rate of 70-130% were evaluated as passing (○).
[0086] From the above results, it was found that in Examples 1 and 2, by providing a sheath made of a predetermined resin composition, high flame retardancy can be ensured even without a flame retardant tape provided between the sheath and the insulated wire, and a LAN cable with satisfactory physical properties such as sheath strength, elongation, and low-temperature characteristics can be obtained. It was also confirmed that Example 2 is a cable that can be made thinner.
[0087] On the other hand, in Comparative Example 1, it was found that sufficient flame retardancy for railway vehicles could not be obtained unless the flame-retardant tape was used.
[0088] The invention made by the inventor has been specifically described above based on the embodiment thereof. However, it goes without saying that the present invention is not limited to the above embodiment, and various modifications can be made without departing from the spirit of the invention. [Explanation of symbols]
[0089] 1 Conductor 2. Insulation layer 3. Insulated Wire 4 braid 5 Sheath 6. Shield 10 LAN cable 50 Test Cable
Claims
1. A LAN cable comprising a twisted pair wire formed by twisting together a plurality of insulated wires having insulating layers, and a sheath covering the outer periphery of the twisted pair wire, The LAN cable has an outer diameter of 8.8 mm or less, the sheath is made of a halogen-free flame-retardant resin composition containing a base polymer, a metal hydroxide, and carbon black; The metal hydroxide is contained in an amount of 180 to 190 parts by mass relative to 100 parts by mass of the base polymer, The carbon black is contained in an amount of 15 to 20 parts by mass relative to 100 parts by mass of the base polymer, The outer diameter of the insulated wire is 1.43 mm or less, the insulating layer has an overall dielectric constant of 2.5 or less; The insulating layer is made of a halogen-free polymer, No flame retardant tape is provided between the twisted pair wire and the sheath. LAN cable.
2. 2. The LAN cable according to claim 1, A LAN cable having a braid between the twisted pair wires and the sheath.
3. 2. The LAN cable according to claim 1, The metal hydroxide is contained in an amount of 180 to 185 parts by mass per 100 parts by mass of the base polymer, and the carbon black is contained in an amount of 15 to 20 parts by mass per 100 parts by mass of the base polymer.
4. 2. The LAN cable according to claim 1, The insulated wire has a structure in which the insulating layer includes a foam layer.
5. 5. The LAN cable according to claim 4, The insulating layer has a three-layer structure, and the total thickness of the three-layer structure is 0.35 to 0.45 mm.
Citation Information
Patent Citations
Non-halogen resin composition, electric wire and cable
JP2020125459A
LAN cable
JP2021064623A